Legal Aspects of Regional and City Development Planning - Asep Jakaria Syifa Ajhara; Ucep Bayu Bastian (GoResearch - Research & Publishing House, 2023)
The practice of urban and regional planning cannot be separated from the legal and administrative aspects of development. The legal aspect determines basic matters such as the legal basis that mandates a planning activity, the rules of how and by whom planning is carried out or the administrative process, how the legality of a plan product, and its law enforcement. Healey (1997) asserts that the planning system can be defined as a system of laws and procedures that establish the basic rules of planning practice. The development of the type of planning adopted or being carried out also affects the formulation of the legal basis of planning activities. Aspects of development administration, which are closely related to bureaucracy, determine the effectiveness and efficiency of urban and regional planning activities. Even more than that, development administration greatly influences the operationalization and successful implementation of a plan. So there is an interactive relationship between law and development administration, as well as between law and development administration with regional and city planning.